Vitamin E supplementation fails to impact measures of oxidative stress or the anaemia of feline chronic kidney disease: a randomised, double‐blinded placebo control study. Issue 2 (22nd January 2016) - Timmons, Rebecca M.; Webb, Craig B.
Abstract: This study was designed to test the hypothesis that supplementation with vitamin E, an antioxidant, in cats with chronic kidney disease (CKD), would reduce oxidative stress and its impact on RBC membrane fragility, resulting in these cats maintaining a greater packed cell volume (PCV) compared with CKD cats not receiving supplementation. Thirty‐six cats with CKD were randomly assigned to receive either daily vitamin E or a placebo for 3 months in a double‐blinded study design. History and physical examination, blood pressure, complete blood count (CBC), PCV, biochemical profile and urinalysis (UA) were determined. Parameters of oxidative stress and osmotic fragility were measured. Cats were administered vitamin E or placebo once daily for 3 months. Cats were then reassessed and the diagnostics were repeated. Twenty‐four cats completed the study, 11 in the vitamin E group and 13 in the placebo group. There were no significant differences between the two groups at the start, or upon completion of the study with regard to biochemical parameters, oxidative stress, erythrocyte osmotic fragility or PCV. None of these parameters changed significantly in either group over the treatment period. Daily supplementation with 30 IU of vitamin E did not affect the measures of oxidative stress or the anaemia seen in cats with CKD. Abstract : This study investigated the effect of vitamin E supplementation in cats with chronic kidney disease. It was determined that daily supplementation of 30 IU of vitamin E failed to impact the anemia of CKD in cats or measures of oxidative stress.